2023
DOI: 10.7759/cureus.37333
|View full text |Cite
|
Sign up to set email alerts
|

Rhabdomyolysis in Critically Ill Patients With COVID-19: A Retrospective Study

Abstract: Introduction: The total number of ICU admissions for COVID-19 patients has increased steadily. Based on the research team's clinical observations, many patients developed rhabdomyolysis, but few cases were reported in the literature. This study explores the incidence of rhabdomyolysis and its outcomes, like mortality, the need for intubation, acute kidney injury, and the need for renal replacement therapy (RRT).Methods: We retrospectively reviewed the characteristics and outcomes of patients admitted to the IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…If rashes had been present, for example, a dermatomyositis would be suspected [ 4 ]. Rhabdomyolysis with SARS-CoV-2 is associated with higher rates of ICU admission, mechanical ventilation, and mortality [ 1 , 3 ]. Persistent fatigue and myalgias have been reported as the long-term debilitating symptoms of the condition [ 8 ], which our patient fortunately did not endure and had a good clinical response likely due to young age and absence of comorbid risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If rashes had been present, for example, a dermatomyositis would be suspected [ 4 ]. Rhabdomyolysis with SARS-CoV-2 is associated with higher rates of ICU admission, mechanical ventilation, and mortality [ 1 , 3 ]. Persistent fatigue and myalgias have been reported as the long-term debilitating symptoms of the condition [ 8 ], which our patient fortunately did not endure and had a good clinical response likely due to young age and absence of comorbid risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…As many as 2.2% of patients affected with SARS-CoV-2 may have rhabdomyolysis, a condition characterized by the breakdown of skeletal muscle [ 1 ] and may be a specific subtype of viral myositis [ 2 ]. It is important to recognize this condition due to mortality rates as high as 30% [ 3 ]. In the setting of acute kidney injury (AKI), fatality can be as high as 40% [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Systemic inflammation, prevalent in these conditions, intensifies muscle degradation, with cytokines both promoting protein breakdown and hampering muscle regeneration [ 86 – 88 ]. One study observed that in 146 COVID-19 patients who developed rhabdomyolysis, approximately 30% died and 40% developed AKI, indicating the systemic effects of muscle breakdown can result in severe consequences for COVID-19 patients [ 89 ].…”
Section: Indirect Effects Of Sars-cov-2 Infection On Bonementioning
confidence: 99%
“…The diffuse myositis observed with SARS-CoV-2 infection and the failure to consistently identify viral particles in myocytes suggests that the myositis is a result of the “cytokine storm” brought on by the infection. When the myositis is severe, the myoglobin released from muscle breakdown can cause a form of kidney failure referred to as rhabdomyolysis [ 95 – 98 ]. The effects of acute kidney failure with SARS-CoV-2 infection will be discussed in a later section.…”
Section: Indirect Effects Of Sars-cov-2 Infection On Bonementioning
confidence: 99%